IMPLEMENTASI ADAPTIVE NEURO FUZZY INFERENCE SYSTEM UNTUK SISTEM SELEKSI PENERIMAAN BEASISWA PADA SMK PRIMA WISATA JAKARTA - Darussalam, Muhammad (LPPM Universitas Nusa Mandiri, 2017)
SMK Prima Travel provides scholarships for some students who are less able and has a learning achievement in school to help the educational process. The purpose of this scholarship is to reduce the number of students who drop out of school due to lack of funds to meet the needs of education, to increase students' motivation and to help students who have economic difficulties. In the selection of scholarship acceptance, there are several assessment criteria, including the average value of report cards, home ownership status, transportation to school, the number of parent income, number of dependents of parents, and the number of siblings. The assessment was performed by the school in a way that is still manual, ie scholarship acceptance selection is based on economic circumstances and does not see the criteria that have been defined so that the results are still less precise and accurate. The neuro-fuzzy approach will be used for screening reception awardees to show that the assessment can be done more accurately and faster when compared to admission scholarship selection system is done manually. Tests on these studies show that the model of the triangular and trapezoidal membership functions have the same accuracy results amounted to 99.7%. While the test results gauss membership function models have accuracy values of 98% and a model gbell membership function has a value of 93.9% accuracy.